2023
DOI: 10.5459/bnzsee.1572
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the torsional behaviour of hollow core slabs

Abstract: There are many applications in buildings in which precast pre-stressed hollow-core (HC) slabs are subjected to shear, torsion, or combined shear and torsion. Nonetheless, extruded HC units contain no transverse reinforcement, being inherently vulnerable to brittle failure modes due to shear and torsional actions. In previous work by the authors, a finite element (FE) modelling approach for HC units failing in shear was developed and validated against experimental test data. This paper aims to extend the applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
0
0
Order By: Relevance
“…Khakimov and S.A. Dmitriev, the effects of the thickness of the protective concrete layer on the bending elements' crack width were investigated. Based on the recent research results [21], the failure of prestressed hollow-core slabs manufactured by the extrusion method was modeled. In other studies [22,23], investigations have revealed aspects of the behavior of prestressed building slabs, considering the changes in their properties and connections.…”
Section: Introductionmentioning
confidence: 99%
“…Khakimov and S.A. Dmitriev, the effects of the thickness of the protective concrete layer on the bending elements' crack width were investigated. Based on the recent research results [21], the failure of prestressed hollow-core slabs manufactured by the extrusion method was modeled. In other studies [22,23], investigations have revealed aspects of the behavior of prestressed building slabs, considering the changes in their properties and connections.…”
Section: Introductionmentioning
confidence: 99%